2021
DOI: 10.1371/journal.pone.0260281
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical compositions and larvicidal activity of nut extracts from Areca catechu Linn against Aedes (Diptera: Culicidae)

Abstract: Background There is a growing need to use green alternative larvicidal control for Aedes larvae compared to chemical insecticides. Substantial reliance on chemical insecticides caused insecticide resistance in mosquito populations. Thus, research for alternate chemical compounds from natural products is necessary to control Aedes larvae. This study explores the analysis of chemical compositions from Areca catechu nut as a potential larvicide for Aedes (Diptera: Culicidae). Methods The Areca catechu nut colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The compounds viz., Hexadecanoic acid, methyl ester; n-Hexadecanoic acid and 9, 12-octadecadienoic acid (Z,Z) were reported while studying bruchid resistant and susceptible lines in chickpea (Reddy et al, 2021) and in blackgram (Ragul et al, 2022) through GC-MS analysis. Bharathithasan et al (2021) also reported insecticidal property of Octadecaenoic acid against insect pest of Areca nut.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The compounds viz., Hexadecanoic acid, methyl ester; n-Hexadecanoic acid and 9, 12-octadecadienoic acid (Z,Z) were reported while studying bruchid resistant and susceptible lines in chickpea (Reddy et al, 2021) and in blackgram (Ragul et al, 2022) through GC-MS analysis. Bharathithasan et al (2021) also reported insecticidal property of Octadecaenoic acid against insect pest of Areca nut.…”
Section: Resultsmentioning
confidence: 94%
“…The compound 9, 12-Octadecadienoic acid, methyl ester was reported against bruchid infestation in chickpea (Reddy et al, 2021). Hexadecanoic acid, 1-(hydroxymethyl)-1, 2-ethanediyl ester and Hexadecanoic acid, 2-oxiranyl methyl ester were known to have insecticidal properties against insect pest of Areca nut (Bharathithasan et al, 2021). Therefore, in the present study, 9, 12-Octadecadienoic acid, methyl ester; Hexadecanoic acid, 1-(hydroxymethyl)-1, 2-ethanediyl ester and Hexadecanoic acid, 2-oxiranyl methyl ester were identified as the compounds responsible for bruchid (Callosobruchus chinensis) resistance in greengram.…”
Section: Resultsmentioning
confidence: 99%
“…These findings contribute to comprehending bacterial volatiles in the rhizosphere and their functions (Yi et al, 2016). The bioactive components of tetradecanoic acid have been employed as additives in insecticides, pest control, insect repellents, and insecticidal agents (Bharathithasan et al, 2021).…”
Section: The Intensity Of Leafs Spot Disease In Greenhousementioning
confidence: 95%
“…The major constituents of this plant, such as bovinic acid and methyl linoleate in hexane and chloroform extracts, have been reported to possess insecticidal activity against the potato bug (Leptinotarsa decemlineata) [20] and herbicidal activity against wild oat (Avena fatua), sun spurge (Euphorbia helioscopia), goosefoot (Chenopodium album), canary grass (Phalaris minor), and knotweed (Rumex dentatus), respectively [21]. On the other hand, in ethyl acetate extract, some chemical constituents such as palmitic and linoelaidic acids, were found to show larvicidal and insecticidal activities against Aedes aegypti Linn and cotton leafworm (Spodoptera littoralis), respectively [22,23]. Moreover, methyl palmitate presents in the water extract exhibited acaricidal activity against Tetranychus cinnabarinus (Boisduval) [24].…”
Section: Potential Use Of Adlay Phytochemicals For Agrochemicalsmentioning
confidence: 99%